The literary and translatory perception of A. N. Ostrovsky's play "Without a dowry" in China - Mengqi Shen; Galina I. Modina (Publishing house "Sreda", 2023)
The article is devoted to the reception of one of the most famous plays of A. N. Ostrovsky in China - "Without a Dowry". The play belongs to the late period of the playwright's work and is characterised by a complex genre. In Russian literary studies it is considered as a socio-psychological drama with a bright lyrical beginning. The aim of the article is to give an idea of the translation, literary and literary perception of the play in China. The author of four versions of the play's translation into Chinese, Chen Bingyi, analyses the peculiarities of the play's translation. It reveals the main aspects of literary research on the play in China and examines the particular understanding of "Without a Dowry" by the playwright and translator Chen Baichen. By comparing the plots of A.N. Ostrovsky's drama and Chen Baichen's drama "Love on a Steep Cliff", the article highlights the influence of the character Katerina from the famous play "The Storm" on the interpretation of the female protagonist and the genre characteristics of "Without a Dowry". The analysis demonstrates that Chinese translators, literary critics, and playwrights collectively perceive this psychological drama by Ostrovsky as a social drama within the historical and cultural context of 1940s China.